Neuroprotective Effect of the Ginsenoside Rg1 on Cerebral Ischemic Injury In Vivo and In Vitro Is Mediated by PPARγ-Regulated Antioxidative and Anti-Inflammatory Pathways. (1st June 2017) - Li, Yang; Guan, Yue; Wang, Ying; Yu, Chun-Lei; Zhai, Feng-Guo; Guan, Li-Xin
Abstract : The ginsenoside Rg1 exerts a neuroprotective effect during cerebral ischemia/reperfusion injury. Rg1 has been previously reported to improve PPAR γ expression and signaling, consequently enhancing its regulatory processes. Due to PPAR γ 's role in the suppression of oxidative stress and inflammation, Rg1's PPAR γ -normalizing capacity may play a role in the observed neuroprotective action of Rg1 during ischemic brain injury. We utilized a middle cerebral artery ischemia/reperfusion injury model in rats in addition to an oxygen glucose deprivation model in cortical neurons to elucidate the mechanisms underlying the neuroprotective effects of Rg1. We found that Rg1 significantly increased PPAR γ expression and reduced multiple indicators of oxidative stress and inflammation. Ultimately, Rg1 treatment improved neurological function and diminished brain edema, indicating that Rg1 may exert its neuroprotective action on cerebral ischemia/reperfusion injury through the activation of PPAR γ signaling. In addition, the present findings suggested that Rg1 was a potent PPAR γ agonist in that it upregulated PPAR γ expression and was inhibited by GW9662, a selective PPAR γ antagonist. These findings expand our previous understanding of the molecular basis of the therapeutic action of Rg1 in cerebral ischemic injury, laying the ground work for expanded study and clinical optimization of the compound.